Effects of thoracic spine manipulation on pressure pain sensitivity of rhomboid muscle active trigger points: a randomized control trial - Bibi Haleema; Huma Riaz (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of study was to determine the effects of thoracic spine manipulation on interscapular pain and pain pressure sensitivity, thoracic mobility and disability due to active myofascial trigger points in rhomboid muscle. Methods: A randomized control trial was conducted at Women Institute of Rehabilitation Sciences Abbottabad, from July to December 2019.Ethical permission was taken fromResearch ethical committee of Riphah international university Islamabad. Participants were selected through non-probability purposive sampling technique as per inclusion criteria. It consisted of 60 participants with forward head posture having active trigger points in rhomboid muscle, with age ranging from 18 to 30 years. The participants were randomly allocated through sealed envelope method into two groups that are experimental and control. Experimental group has received thoracic manipulation along with conventional physical therapy (CPT) whereas control group has only received CPT including manual pressure release and therapeutic exercise. Intervention was applied with 2 sessions / week with 3 weeks in total. Pre and Post assessment was done with outcome measurement tools comprised of Numeric pain rating scale (NPRS) for pain severity, Algometry for pain pressure threshold(PPT), Inclinometer for Range of movement(ROM) and Neck disability index (NDI) for associated disability. Data analysis was done using SPSS-20 version. Results: Between group analysis has shown significant improvement of pain & pain pressure sensitivity with p value <0.01 and <0.05 respectively. All outcome measures have shown significant difference in pre post treatment (p<.000) in both groups. Continuous...